CircDLPAG4/HECTD1 mediates ischaemia/reperfusion injury in endothelial cells via ER stress. Issue 2 (1st February 2020) - Chen, Lulu; Luo, Wei; Zhang, Wei; Chu, Han; Wang, Jing; Dai, Xiaoniu; Cheng, Yusi; Zhu, Tiebing; Chao, Jie
ABSTRACT: Background : Vascular endothelial cell dysfunction, characterized by cell apoptosis and migration, plays a crucial role in ischaemia/reperfusion (I/R) injury, a common aspect of cardiovascular diseases. Recent studies have suggested that non-coding RNAs, such as circular RNAs (circRNA), play a role in cell dysfunction in I/R injury, although the detailed mechanism is unclear. Methods : Human umbilical vein endothelial cells (HUVECs) were used for in vitro I/R model. Protein expression was detected by western blotting (WB) and immunocytochemistry. The CRISPR/Cas9 system, WB, cell viability assays, Hoechst staining and a 3D migration model were used to explore functional changes. RNA expression was evaluated using quantitative real-time PCR and a FISH assay combined with lentivirus transfection regulating circRNAs and miRNAs. A mouse myocardial I/R model using C57 mice was established to confirm the in vitro findings. Results : In HUVECs, I/R induced a significant time-dependent decrease in HECTD1 associated with an approximately 45% decrease in cell viability and increases in cell apoptosis and migration, which were attenuated by HECTD1 overexpression. I/R-induced upregulation of endoplasmic reticulum stress was also attenuated HECTD1 overexpression. Moreover, miR-143 mimics inhibited HECTD1 expression, which was restored by circDLGAP4 overexpression, providing insight as to the molecular mechanism of I/R-induced HECTD1 in endothelial cell dysfunction. Conclusion : Our results suggest a critical role for circDLGAP4 and HECTD1 in endothelial cell dysfunction induced by I/R, providing novel insight into potential therapeutic targets for the treatment of myocardial ischaemia.